Kehamilan Dengan Kanker Paru - Mikhail Nurhari; Bobby Indra Utama (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Background: Pulmonary cancer is the most prevalent malignancy in the world. Management of cancer in pregnancy creates a dilemma. Patients who choose to continue her pregnancy have to delay her cancer treatment in order to protect the fetus.Objectives: To review the case of pulmonary cancer in pregnancy presented in M. Djamil Central General Hospital Padang.Case: A 24-year-old woman came to the M. Djamil Central General Hospital Padang on September 12th 2017 with diagnosis of G2P1A0L1 37-38 weeks of term pregnancy + history of previous CS + Pulmonary Cancer. Patients have been diagnosed with Pulmonary Cancer based on bronchoscopy. Chemotherapy was initially planned for 9 times, but after the third chemotherapy the patient was known to be pregnant. Patient was encouraged to terminate her pregnancy but the patient refused and chose to continue the pregnancy.Conclusions: Pregnancy with Pulmonary cancer raises its own problems in its management. Practitioners must provide optimal treatment for the mother while protecting the fetus.